Validity of Leukocyte Esterase Dipstick Test Compared to Gold Standard Urine Culture in Hospitalized Children Suspected of Urinary Tract Infections - Alya Rahmatika Sabtyastuti; Raja Iqbal Mulya Harahap; Rini Rossanti; Ahmedz Widiasta; Arif Tri Prasetyo (RSUP Dr. Kariadi, 2025)
BACKGROUND : Urinary tract infection (UTI) is an illness that affects specifically the bladder and other structures in the urinary tract. The leukocyte esterase dipstick examination is recognized for its high sensitivity but limited specificity. Additional diseases, like glomerulonephritis, can yield positive outcomes in this test. This research was conducted to determine the validity of leukocyte esterase examination in urine culture in children suspected of urinary tract infection. AIMS : To assess the accuracy of leukocyte esterase testing on urine culture in children suspected of having a . METHOD : This study employed a diagnostic test method with a cross-sectional design. Research data were obtained from medical record of pediatric patients admitted to RSUP dr. Hasan Sadikin from 2022 to 2023 with suspected urinary tract infection. RESULT : The values for the diagnostic test results are follows true positive 80%, false positive 51%, true negative 25%, and false negative 40% respectively. The calculations reveal that the leukocyte esterase dip stick has a sensitivity of 67%, specificity of 33%, positive predictive value (PPV) of 61%, negative predictive value (NPV) of 38%, a positive likelihood ratio of 1.56, and a negative likelihood ratio of 0.625. CONCLUSION : This study indicates that the leukocyte esterase dipstick examination has a sensitivity rate of 67%, specificity rate of 33%, PPV of 61%, and NPV value of 38%. The leukocyte esterase dipstick has a high sensitivity level and a low specificity level.